THE ROLE OF ALEXANDER FEYNBERG'S WORK IN UZBEK LITERATURE - Norboyeva Zuhraxon Alijon qizi (TADQIQOTLAR, 2025)
Abstract: This article gives information regarding Alexander Fainberg's life, artistic endeavors, and cultural legacy. It describes the poet's contributions to Uzbek literature  and  culture,  especially  his  translations,  poetry  collections,  and  cinematic achievements.